English Analisis Peramalan Permintaan Beras pada SPPG dan Proyeksi Kebutuhan untuk Program Makan Bergizi Gratis di Kota Bandung: Analisis Peramalan Permintaan Beras di SPPG dan Proyeksi Permintaan untuk Program Makanan Bergizi Gratis di Kota Bandung - MHD Wahyu Riandani; Agus Purnomo; Maniah (Institut Ilmu Sosial dan Manajemen STIAMI, 2026)
The Free Nutritious Meal Program (MBG) is expected to significantly increase food demand, particularly for rice as the main staple in meal preparation. However, studies linking operational kitchen data with city-level rice demand projections remain limited. This study aims to analyze operational rice demand at Nutrition Fulfillment Service Units (SPPG) in Bandung City and to project rice demand under different program expansion scenarios. A quantitative approach was employed using time series forecasting by comparing ARIMA, Holt-Winters, and Default Forecast (Mean in Window) models. Model performance was evaluated using RMSE and MAPE indicators. The dataset consists of operational data from 26 SPPG units, including rice purchases, meal portions produced, and the frequency of rice-based menus during April 2025–January 2026. Results show that ARIMA provides the best forecasting performance (RMSE 3859.634; MAPE 15.08%). Consumption calibration indicates rice usage of approximately 0.055–0.066 kg per portion. Scenario projections suggest that MBG expansion may substantially increase rice demand, highlighting the need to integrate program planning with regional food security policies.